Analysis of Comfort Levels of Men’s Pants Patterns Size L Soekarno, Balai Latihan Kerja, and Citra Tailor Systems - Eko Febrianto; Hapsari Kusumawardani; Agus Hery Supadmi Irianti (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
This study aims to analyze the methods of making patterns for men's trousers and the comfort level of men's trousers patterns in size L created using the Soekarno system, the Balai Latihan Kerja system, and the Citra Tailor system. This research is descriptive with a quantitative approach. Data collection was done using expert panel assessment sheets. The research results are as follows: 1) Significant differences among the three pattern systems lie in the creation of the back pattern, specifically in the waistline and thigh lines, which determine the comfort of the hip circumference. 2) The comfort level of men's trousers patterns in size L using the Soekarno system, in terms of static comfort level, shows overall results falling into the comfortable category. Similarly, the results for kinetic comfort level fall into the comfortable category overall. 3) The comfort level of men's trousers patterns in size L using the Balai Latihan Kerja system, in terms of static comfort level, shows overall results falling into the less comfortable category. Similarly, the results for kinetic comfort level fall into the less comfortable category overall. 4) The comfort level of men's trousers patterns in size L using the Citra Tailor system, in terms of static comfort level, shows overall results falling into the less comfortable category. Similarly, the results for kinetic comfort level fall into the less comfortable category overall. This research is expected to be used as a reference for further researchers.